2016
DOI: 10.1021/acs.energyfuels.6b02369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trace Nitrogen Oxides on Natural Gas Oxidation: Flow Reactor Measurements and Kinetic Modeling

Abstract: The reactivity-promoting effect of trace nitrogen oxides (NO x ) on post-induction oxidation of a synthetic natural gas (2% ethane in methane) has been experimentally studied in a high-pressure laminar flow reactor (HPLFR) at 10 ± 0.1 atm, nominal reaction temperature of 818 ± 5 K, and several equivalence ratios (φ ∼ 0.5, 1.0, and 2.0). Each set of experimental measurements was simulated using several literature C0–C2 + NO x kinetic models, both recent and legacy, using approaches shown to lead to robust inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Understanding the influence of NO x on combustion kinetics of hydrocarbon fuels is important to properly model combustion in internal combustion engines and gas turbines with exhaust gas recirculation, partially as a result of the presence of NO x in recirculated exhaust gas. Oxidation of hydrocarbon fuels with NO x addition has long been investigated, including H 2 , CH 4 , C 2 hydrocarbons, natural gas, and higher hydrocarbons. , It has been shown that even a small amount of nitrogen oxides can have a significant effect on the combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the influence of NO x on combustion kinetics of hydrocarbon fuels is important to properly model combustion in internal combustion engines and gas turbines with exhaust gas recirculation, partially as a result of the presence of NO x in recirculated exhaust gas. Oxidation of hydrocarbon fuels with NO x addition has long been investigated, including H 2 , CH 4 , C 2 hydrocarbons, natural gas, and higher hydrocarbons. , It has been shown that even a small amount of nitrogen oxides can have a significant effect on the combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 23 found that a condition combined of fuel-rich atmosphere and relatively low temperature (700–900°C) could cause the NO oxidation to form NO 2 , and the generated NO 2 could even exceed 50% of the total NO x emission. Alam et al 24 suggested this NO 2 formation was via the reaction R1, and a subsequent reaction R2 would occur immediately, causing an acceleration on CH 3 bt no NO 2 emission. However, as the oxidation for CH 4 here is very poor, CH 3 formation could be inhibited to prevent NO 2 consumption via R2, causing the accumulation of NO 2 in flue gas.…”
Section: Resultsmentioning
confidence: 99%
“…CH 3 NO 2 can withstand high temperatures; therefore, it can act as a sink for NO 2 under combustion-relevant conditions. In a recent work, Alam et al highlight the relevance of CH 3 NO 2 chemistry in altering the kinetics of hydrocarbons oxidation in NO x -perturbed environments. However, its formation and degradation highly depend on the chemical environment .…”
Section: Results and Discussionmentioning
confidence: 99%